Local Food Systems and Rural Development in Bulgaria - Peneva, Mariya; Kazakova-Mateva, Yanka (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2015)
Recently there has been a renewed interest in alternatives to shorten the food supply chain, allowing more direct links between producers and consumers and localizing food systems. This paper examines alternative local food chains as part of rural development and how to encourage and facilitate their growth in order to contribute to rural vitality and sustainable agriculture. It focuses on some research findings of the Bulgarian team in the project entitled “Farming transitions: Pathways towards regional sustainability of agriculture in Europe” (FarmPath), financed by the 7th FP of the EC. The innovative initiatives that define development of new alternative forms of agricultural local food supply chains, combined with nature-friendly production practices, rural tourism, traditional food production and development of the territory of three rural areas are presented and analysed. The sustainability dimensions that the alternative supply chains may lead up to in the rural regions were also drawn.